Penerapan Metode Penelitian Hukum Normatif dalam Studi Tindak Pidana Korupsi di Indonesia (International Forum of Researchers and Lecturers, 2026)
This study aims to explain the application of normative legal research methods in analyzing corruption in Indonesia. The normative legal research method is used because the main focus of this study lies in the study of laws and regulations, legal doctrine, and court decisions related to corruption. Through this approach, the study highlights how written legal norms are implemented in law enforcement practices, as well as their effectiveness in tackling corruption, which has become a systemic problem in Indonesia. This study also evaluates the role of existing regulations in providing legal protection for the interests of the state and society, and identifies weaknesses in the legal system that are often exploited by perpetrators of corruption to avoid punishment. By focusing on the application of legal norms in enforcing corruption laws, this study also analyzes the development of jurisprudence related to corruption and the contribution of legal doctrine to more effective law enforcement. This study is expected to provide deeper insight into the strengths and weaknesses of the legal system in Indonesia, as well as provide recommendations for improving the judicial system in handling corruption cases. The results of this study are expected to enrich legal studies in Indonesia, especially in the field of criminal law and legislation related to corruption.